Modality compatibility biases voluntary choice of response modality in task switching - Fintor, Edina; Poljac, Edita; Stephan, Denise N.; Koch, Iring (Psychological research, 2020)
The term modality compatibility refers to the similarity between stimulus modality and the modality of response-related sensory consequences (e.g., vocal responses produce auditory effects). The previous results showed smaller task-switching costs when participants switched between modality compatible tasks (auditory–vocal and visual–manual) compared to switching between modality incompatible tasks (auditory–manual and visual–vocal). In the present study using a voluntary task-switching paradigm (VTS), participants chose the response modality (vocal or manual) to indicate the location of either a visual or an auditory stimulus. We examined whether free task choices were biased by modality compatibility, so that modality compatible tasks are preferred in VTS. The choice probability analysis indicated that participants tended to choose the response modality that is compatible to the stimulus modality. However, participants did not show a preference to repeat a stimulus–response (S–R) modality mapping, but to switch between modality compatibility (i.e., from S–R modality compatible mapping to S–R modality incompatible mapping and vice versa). More interestingly, even though participants freely chose the response modality, modality compatibility still influenced task-switching costs, showing larger costs with modality incompatible mappings. The finding that modality compatibility influenced choice behaviour suggests components of both top–down control and bottom–up effects of selecting a response modality for different stimulus modalities.